2018
DOI: 10.1088/1361-6544/aae175
|View full text |Cite
|
Sign up to set email alerts
|

Large dispersion, averaging and attractors: three 1D paradigms

Abstract: The effect of rapid oscillations, related to large dispersion terms, on the dynamics of dissipative evolution equations is studied for the model examples of the 1D complex Ginzburg-Landau and the Kuramoto-Sivashinsky equations. Three different scenarios of this effect are demonstrated. According to the first scenario, the dissipation mechanism is not affected and the diameter of the global attractor remains uniformly bounded with respect to the very large dispersion coefficient. However, the limit equation, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 63 publications
(107 reference statements)
1
13
0
Order By: Relevance
“…By this reason, it looks natural to utilize the rapid in time oscillations caused by this dispersive term. To this end, following, say, [10] (see also references therein), we do the change of variables Zn(t) = e iωnt zn(t).…”
Section: Key Estimates For the Linearized Equationmentioning
confidence: 99%
See 3 more Smart Citations
“…By this reason, it looks natural to utilize the rapid in time oscillations caused by this dispersive term. To this end, following, say, [10] (see also references therein), we do the change of variables Zn(t) = e iωnt zn(t).…”
Section: Key Estimates For the Linearized Equationmentioning
confidence: 99%
“…Thus, equation (222) preserves all good properties of equation 2.21, so it is sufficient to prove the unique solvability of (2.22) in the space L 2 (R − , H I ). This equation has an essential advantage since it contains an explicit rapidly oscillating term with zero mean, so by the classical averaging theory (see [10] and references therein), we expect that this term will be averaged to zero and the solvability of (2.22) for a general β(t) should follow from the particular case β = 0 (where it is obvious). Let us justify this idea.…”
Section: Key Estimates For the Linearized Equationmentioning
confidence: 99%
See 2 more Smart Citations
“…a large amount of dispersion) can regularize chaotic dynamics for any system length L , as solutions are observed to be attracted to nonlinear travelling waves. Surprisingly, third-order dispersion acts as a destabilizing mechanism for this equation, competing with the stabilizing nonlinear term—it hinders the transfer of energy from low to high wavenumbers, and consequently analyticity of solutions reduces as δ is increased (see [ 61 ] for a discussion of this for the 1D case). Turning to the 2D problem, Toh et al [ 41 ] and Indireshkumar & Frenkel [ 42 ] observed pulse solutions of ( 1.3 ) for large values of dispersion on large periodic domains—the usual streamwise cellular structures are found to be unstable and give way to the 2D pulses.…”
Section: Computations When Dispersion Is Presentmentioning
confidence: 99%